Performan Domba Lokal Jantan yang Diberikan Ransum Mengandung Pelepah Nipah Hasil Biofermentasi - Suryadi Suryadi; Farizaldi Farizaldi; Afdal Afdal (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of biofermented nipah fronds as a substitute for field grass on the performance of local male sheep. Fermented nipah fronds used in rations is the best fermented with a storage time of 15 days. The level of replacement of field grass  with processed nipah palm fronds is 0, 10, 20 and 30 percent. This study used a randomized block design (RAK) with 4 treatments and was repeated 3 times. Treatment rations were arranged based on the body weight of male local sheep. The variables measured were ration consumption, body weight gain and ration conversion. The results showed that ration consumption, body weight gain and ration conversion had no significant effect (P>0.05) due to the replacement treatment of fermented nipah midrib with can field grass. It was concluded that the nipah fronds produced by biofermentation with local microorganisms (MOL) can be used 10 – 30 percent in  the rations as a substitute for field grass without reducing the performance of local male sheep.